Detection of Aflatoxin in Poultry Feed and Feed Materials through Immuno Based Assay from Different Poultry Farms and Feed Factories in Bangladesh - Lubna, Mahbuba Akter; Debnath, Mita; Hossaini, Farzana (Bangladesh Journal of Microbiology, 2019)
Current study investigated the occurrence of aflatoxin contamination in poultry feed and feed materials in different poultry farms and feed factories in Bangladesh. A total of 100 samples of finished feed and raw feed materials were collected and tested through direct competitive Enzyme-Linked Immunosorbent Assay (ELISA) for total aflatoxin detection. Overall, 97% samples (n=97/100) in our study, were found positive for aflatoxin contamination. Among finished feed categories, layer grower feed contained highest level of aflatoxin with a mean value of 21.64 ppb whereas layer feed was less susceptible for aflatoxin contamination (mean value 9.49 ppb). Between raw feed materials, maize samples were highly contaminated (n=15/15, 100%) with aflatoxin while 86.67% soybean samples showed positive result. Twenty one percent (21%) of the samples in our study contained aflatoxin concentration more than the acceptable limit employed by USFDA and many other countries which might pose severe health risk to poultry and human consumer. Proper surveillance and immediate control measures should be taken to ensure safe poultry feed and feed materials. Bangladesh J Microbiol, Volume 35 Number 1 June 2018, pp 75-78